Spiritual renewal and the healing of creation. Issue 4 (October 2019) - Effa, Allan
This article is a biblical exploration of the interplay between spiritual renewal of the people of God and the spirit's work of renewing and healing creation. On the flip side, it highlights the biblical theme of environmental distress as a consequence of human disobedience. Beginning with God's social covenant with Israel, the article moves to a primary focus on ecological texts in the book of Isaiah. Isaiah's vision encompasses climactic catastrophes, the plight of animal species, the integrity and pollution of the soil, deforestation, and the languishing and flourishing of the entire created order. Isaiah's pneumatology uniquely portrays the work of the Creator Spirit as one of renewing and breathing new life into a suffering world. This article offers a fresh exegesis of the ecological texts of Isaiah and considers a number of practical implications for mission in light of the environmental challenges particularly unique to Canada's province of Alberta. It concludes by charting some of the ways people who exhibit the fruit of the spirit might alter their lifestyles and contribute to the spirit's work of healing creation.